Problems connected with a philosophical method - Besler, Gabriela (Folia Philosophica, 2007)
In this paper I tried to give a metaphilosophical characteristic of a philosophical method. I define a philosophical method, indicate its components, describe its relation to the subject matter and aim of investigation, and list difficulties connected with it. I assume that a philosophical method differs from the scientific one. Each philosophical method is based on philosophical theses. This connection between philosophical theses and an assumed philosophical method is shown on the example of the method of the philosophy of God. At the end of my paper I formulated an algorithm which can be used in examining a philosophical method.